Effect of dryer fabric structure on the performance of contact paper drying. Issue 7 (19th May 2019) - Forughi, Amir Farzad; Green, Sheldon; Stoeber, Boris
Abstract: Existing measurement techniques have prevented extensive investigations of the effect of dryer fabric structure on contact drying of paper. Using a novel optical measurement method, the moisture content (MC) of paper can be accurately quantified at high spatial and temporal resolution while it is sandwiched between the heater surface and the dryer fabric. To study the paper drying process, an experimental setup is designed to simulate realistic conditions of a typical paper dryer while providing optical access for the measurement system. Ten commercially available fabrics manufactured by weaving synthetic filaments are used in the investigations. The 3D structure of the fabrics is characterized using optical coherence tomography (OCT). The fabrics are used in the experiments to investigate the effects of the filament structure and paper/fabric contact on the drying process. It is shown the fabric structure affects the drying rate and the drying time. Fabrics that have a relatively large drying rate at high paper MC may have a relatively small drying rate at low levels of MC. The contact area and 3D arrangement of the filaments have the greatest impact on the drying process. Adjacent filaments result in larger blocked regions of the paper surface, which reduces the drying rate. The spatial distribution of moisture as a function of time reveals that frequent rewetted spots appear during the drying. These rewetting spots are caused by reabsorption of water condensed on the fabric filaments.